Local Artificial Boundary Conditions for the Incompressible Viscous Flow in a Slip Channel (Journal of Computational Mathematics, 2021)
In this paper we consider numerical simulation of incompressible viscous flow in an infinite slip channel. Local artificial boundary conditions at an artificial boundary are derived by the continuity of velocity and normal stress at the segment artificial boundary. Then the original problem is reduced to a boundary value problem on a bounded computational domain. Numerical example shows that our artificial boundary conditions are very effective.